UPAYA EDUKASI RISIKO OBESITAS “RETAS” PADA KELUARGA DI WILAYAH KOTA SURABAYA - Putri, Linta Meyla; Tjokro, Silvia Haniwijaya; Wijaya, Hermanto (PPM STIKES Adi Husada, 2023)
Introduction & Aim: While the issue of malnutrition hasn't been completely overcome, the issue of overweight and obesity seems to be becoming worse. Obesity is a phenomenon similar to an iceberg that appears straightforward on the surface. If not treated right once, it would endanger the sustainability of future generations. Families and their members will have more access to complete health care. The aim of this activity is to carry out extensive community service projects that educate about the risks of obesity using a family-centered approach. Method of Activity: Educational Activities